Biorefinery Approaches For Production Of Cellulosic Ethanol Fuel Using Recombinant Engineered Microorganisms - Malinee Sriariyanun; Marttin Paulraj Gundupalli; Vanarat Phakeenuya; Theerawut Phusamtisampan; Yu-Shen Cheng; Ponnusami Venkatachalam (Journal of Applied Science and Engineering, 2024)
Cellulosic ethanol has been gaining high attention due to its potential to reduce the greenhouse gas emission and cut down the world dependence on fossil fuels. Biorefinery approach for cellulosic ethanol has advantages due to its non-food competing status, natural abundance and benefit to decrease the combustion of agricultural wastes after harvesting seasons. Due to the recalcitrant structure of lignocellulose biomass, pretreatment and hydrolysis are critical to determine the economic viability of the process because they influence the conversion rate of fermentable sugars and, subsequently, final product i.e. ethanol. Therefore, the design for the process to compromise fermentation and upstream process is also essential. With all constraints exist when using harsh conditions during pretreatment, the recombinant engineered microorganisms have been developed and applied as biocatalysts during fermentation. To achieve the maximum production efficiency, different strategies of recombinant engineered microbes include expression optimization to modify the metabolic pathway, modification of secretion and transportation routes, improvement of stress tolerance, and utilization of both C5 and C6 sugars. This review provides the development and current status of cellulosic ethanol production via biorefining process by genetic engineered microbes with a focus on the technological aspects. The remaining challenges, perspective, and economical feasibility of the process are also discussed.